(untitled) (Scientific journal of the Fergana State University, 2025)
Most of the soils found in Uzbekistan are suitable for building a garden. It is possible to build a garden only by improving the reclamation of marshy and saline soils, that is, spending a lot of money. Most fruit crops grow best on cultivated gray soils with medium to light sandy loam soils. When planting a garden, it is advisable to choose rich in nutrients, grassy, non-saline lands with deep gray soil so that trees grow well and produce abundant crops. Lands with standing water are not suitable for fruit trees, especially trees with deep roots. In such soils, trees grow well at first, but after their root system reaches the seepage water, the growth of the tree slows down and the tree begins to gradually dry out.